Postcolonialism and the Study of Religion: Dissecting Orientalism, Nationalism, and Gender Using Postcolonial Theory - Goulet, Nicole (Religion compass, 2011)
Postcolonialism in relation to the study of religion is most greatly informed by the development of postcolonial theory. While postcolonial theory is diverse in its methodological approach and content, the overarching concern is identifying colonialist constructions of knowledge (what Edward Said refers to as, ‘orientalism’) as they were used to justify and maintain the subordination of colonized groups. In particular, colonialist assumptions about religion as rooted in Judeo-Christian morality are challenged by postcolonial theory, giving rise to new understandings of religious responses to the Empire. Postcolonial theorists have, in different ways, called to question these constructions of knowledge by critically evaluating the impact of these formulations as they pertain to religious ideologies and institutions. Further, by questioning key categories such as ‘religion’ and ‘the sacred’, as well as identifying responses to colonial rule in the form of nationalism, theorists have noted the ways in which women and the lower classes in particular have been impacted.